PENGARUH KUALITAS LAYANAN DAN KOMUNIKASI PEMASARAN TERHADAP KEPUTUSAN PENGAMBILAN KREDIT PEGAWAI NEGERI SIPIL - Ahlansyah Ahlansyah; Hasanuddin Bua; Noval Nur (Pascasarjana Universitas Halu Oleo, 2019)
This research intends to find the simultaneous and partial effect of service quality and marketing communication on redit taking decision among PNS at PT. BPD Bank Sultra, Branch Wakatobi. This research is one of explanatory researches, with the population of all civil servants as customers who take multipurpose credits at PT. BPD Bank Sultra, Branch Wakatobi in 2018 with a total 1,849 employees, the sample size was 95 respondents collected by the Slovin method. Then, respondents were taken by accidental sampling. The analytical tool used is multiple regression. The result showed that service quality and marketing communication had significant effects on PNS credit taking decision at PT. BPD Bank Sultra Branch Wakatobi, both simultaneously and partially.Keywords: service quality, marketing communication, purchasing decision